2008
DOI: 10.1126/science.1160741
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a-Mediated Formation of Phosphatidylinositol 4,5-Bisphosphate Regulates LRP6 Phosphorylation

Abstract: The canonical Wnt-β-catenin signaling pathway is initiated by induction of phosphorylation of one of the Wnt receptors, low density lipoprotein receptor-related protein (LRP) 5/6, at Thr 1479 and Ser 1490 . We identified, by screening a human kinase siRNA library, phosphatidylinositol 4-kinase type II (PI4KII) α and phosphatidylinositol-4-phosphate 5-kinase type I (PIP5KI) as required for Wnt3a-induced LRP6 phosphorylation at Ser 1490 in mammalian cells and confirmed that these kinases are important for Wnt si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
237
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(252 citation statements)
references
References 22 publications
12
237
0
3
Order By: Relevance
“…In this study, we report that regulation of PI4KIIa expression can markedly influence the autophosphorylation of HER-2 at Tyr1248, which may impact members of the signaling pathway downstream of HER-2, such as PI3K and ERK, therefore contributing to the accumulation of HIF-1a, a very important molecule for tumor-induced angiogenesis ( Figure 5). It was also interesting to discover that the effect of PI4KIIa on HIF-1a is subtype specific and kinase activity dependent (Figure 4), similar to the effects of PI4KIIa on the Wnt signaling pathway and on adaptor complex-1 and adaptor complex-3 functions (Wang et al, 2003;Craige et al, 2008;Pan et al, 2008). Although we are still not clear about the detailed mechanism, we hypothesize that the effect of PI4KIIa on the HER-2 signal transduction cascade may Figure 6 A model for the mechanism of PI4KIIa action in tumor growth.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In this study, we report that regulation of PI4KIIa expression can markedly influence the autophosphorylation of HER-2 at Tyr1248, which may impact members of the signaling pathway downstream of HER-2, such as PI3K and ERK, therefore contributing to the accumulation of HIF-1a, a very important molecule for tumor-induced angiogenesis ( Figure 5). It was also interesting to discover that the effect of PI4KIIa on HIF-1a is subtype specific and kinase activity dependent (Figure 4), similar to the effects of PI4KIIa on the Wnt signaling pathway and on adaptor complex-1 and adaptor complex-3 functions (Wang et al, 2003;Craige et al, 2008;Pan et al, 2008). Although we are still not clear about the detailed mechanism, we hypothesize that the effect of PI4KIIa on the HER-2 signal transduction cascade may Figure 6 A model for the mechanism of PI4KIIa action in tumor growth.…”
Section: Discussionmentioning
confidence: 79%
“…Recent evidence suggests that PI(4)P produced by PI4KIIa has an independent function in its own right beyond that of generally providing a substrate for PI3K. It has been reported that PI4KIIa is important for Wnt signaling in Xenopus embryos and interacts with Dvl (Pan et al, 2008;Qin et al, 2009). Waugh et al (2003) reported that PI4KIIa colocalized with valosincontaining protein, a potential prognostic marker for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…PI4K, together with PIP5K, rapidly produces PIP 2 after Wnt stimulation and enhances the phosphorylation of LRP5/6 and oligomerization of Dishevelled and LRP5/6 (Pan et al, 2008). Proteomic analysis also showed that Dishevelled interacts with PI4K, Rho, and even G α13 , after Wnt stimulation (Yokoyama, 2012).…”
Section: Resultsmentioning
confidence: 95%
“…Two lipid kinases, phosphatidylinositol 4-kinase type II (PI4KIIa) and phosphatidylinositol-4-phosphate 5-kinase type I (PIP5KI), which are bound and activated by DVL, mediate Wnt-induced PIP2 ( phosphatidylinositol 4,5-bisphosphate) production that promotes LRP6 phosphorylation by GSK3 and CK1 (Pan et al 2008;Qin et al 2009). One model suggests that PIP2 enhances LRP6 aggregation/signalosome formation (see below) and thereby phosphorylation (Pan et al 2008).…”
Section: Lrp6 Phosphorylation: Roles Of Pip2 G-protein and Other Kimentioning
confidence: 99%
“…One model suggests that PIP2 enhances LRP6 aggregation/signalosome formation (see below) and thereby phosphorylation (Pan et al 2008). An alternative mechanism has been suggested by a study of WTX/ Amer1, which is an X-linked tumor suppressor in Wilms tumor.…”
Section: Lrp6 Phosphorylation: Roles Of Pip2 G-protein and Other Kimentioning
confidence: 99%